The efficacy of combining antibiotic treatment with topical intranasal steroid administration in the treatment of chronic otitis media with effusion - Karlidag, Turgut; Kaygusuz, Irfan; Gök, Uzeyir; Yalçin, Sinasi; Keleş, Erol; Oztürk, Levent (My University, 2002)
OBJECTIVES: We evaluated the efficacy of antibiotic treatment with or without topical administration of intranasal budesonide in chronic otitis media with effusion (OME). PATIENTS AND METHODS: The study included 62 patients (age range 2 to 12 years) with chronic OME. The patients were randomly assigned to three groups, namely, antibiotic treatment (20 patients, ampicillin/sulbactam, 25 mg/kg/daily), antibiotic treatment combined with intranasal budesonide (20 patients, 200 mg/daily), and no treatment (22 patients). All patients and families were questioned regarding the presence of allergy, frequent upper respiratory tract infections, passive smoking, low birth weight, and pre-school nursery attendance. Otoscopic examination findings and the results of tympanograms obtained at the time of diagnosis, and at the end of four and eight weeks of treatment were evaluated. RESULTS: At the end of eight weeks, significant improvement in tympanograms and otoscopic findings was obtained in both groups when compared with the control group (p<0.05). Resolution rates were 24% (9/37 ears), 39% (14/36), and 5% (2/40) with antibiotic, budesonide, and no treatment groups, respectively. Although budesonide treatment was associated with a higher rate of resolution of effusion compared to that of antibiotic alone, this did not reach significance (p>0.05). CONCLUSION: Further studies with larger patient series are required to better evaluate the efficacy of antibiotic treatment and topical intranasal steroid administration in chronic OME.
Efüzyonlu otitis media tedavisinde antibiyotik ile birlikte intranazal steroid kullaniminin etkinligi.
Keywords: Acoustic Impedance Tests; Administration, Intranasal; Administration, Oral; Ampicillin; Anti-Inflammatory Agents; Budesonide; Child; Child, Preschool; Chronic Disease; Drug Therapy, Combination; Female; Humans; Male; Otitis Media with Effusion; Sulbactam; Treatment Outcome; ampicillin; antiinflammatory agent; budesonide; sulbactam; sultamicillin; acoustic impedance; article; child; chronic disease; clinical trial; controlled clinical trial; controlled study; drug combination; female; human; intranasal drug administration; male; oral drug administration; pathology; preschool child; randomized controlled trial; secretory otitis media; treatment outcome